Effect of Mikania cordata (Burm) B. L. Robins on NonSpecific Immune Response of Catla catla (Hamilton, 1822) Against Aphanomyces invadans - Kumar, Vikash Kumar; Roy, Suvra Roy; Barman, Debtanu Barman (Fishery Technology, 2025)
The study was conducted to evaluate the efficacy of Mikania cordata leaf powder on non-specific immune response and disease resistance of Catla catla fingerlings against Aphanomyces invadans infection. M. cordata extract was incorporated in the diet (at 0, 1, 2 and 3%) of C. catla fingerlings (19Â±0.95 g). Blood and serum sampling was carried out on 0th , 14th, 28th and 42nd days of feeding trials to determine Nitroblue tetrazolium (NBT) levels and myeloperoxidase activity. The results revealed that fishes fed with M. cordata extract showed significant increased in NBT levels and myeloperoxidase activity when compared to the control group (p